The Public Health Costs of Job Loss - Andreas Kuhn; Rafael Lalive; Josef Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
We study the short-run effect of involuntary job loss on comprehensive measures of public health costs. We focus on job loss induced by plant closure, thereby addressing the reverse causality problem of deteriorating health leading to job loss as job displacements due to plant closure are unlikely caused by workers' health status, but potentially have important effects on individual workers' health and associated public health costs. Our empirical analysis is based on a rich data set from Austria providing comprehensive information on various types of health care costs and day-by-day work history at the individual level. Our central findings are: (i) overall expenditures on medical treatments (hospitalizations, drug prescriptions, doctor visits) are not strongly affected by job displacement; (ii) job loss increases expenditures for antidepressants and related drugs, as well as for hospitalizations due to mental health problems for men (but not for women); and (iii) sickness benefits strongly increase due to job loss.
Keywords: I12; I19; J28; J65; 330; social cost of unemployment; health; job loss; plant closure